2013
DOI: 10.1590/abd1806-4841.20132164
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine detection for the diagnosis of chromium allergy

Abstract: BACKGROUNDPatch testing remains the gold standard method for the identification of the etiologic agent of allergic contact dermatitis. However, it is a subjective, time-consuming exam whose technique demands special care and which presents some contraindications, which hamper its use. In a recent study, we showed that the proliferation assay can suitably replace patch testing for the diagnosis of chromium allergy, which had been previously demonstrated only for nickel allergy. In this study, we try to refine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Lymphocyte proliferation testing is an in vitro assay that evaluates lymphocyte antigen recall . Recent studies have suggested that production of the cytokine IL‐13 may be used to diagnose chromium‐allergic contact dermatitis, and that interferon‐γ, IL‐2, IL‐5 and IL‐12 may serve to further establish an accurate diagnosis . It was recently suggested that cellular in vitro responses, determined with the lymphocyte transformation test, could discriminate between sensitized individuals with and without clinically manifest allergy .…”
Section: Patch Testingmentioning
confidence: 99%
“…Lymphocyte proliferation testing is an in vitro assay that evaluates lymphocyte antigen recall . Recent studies have suggested that production of the cytokine IL‐13 may be used to diagnose chromium‐allergic contact dermatitis, and that interferon‐γ, IL‐2, IL‐5 and IL‐12 may serve to further establish an accurate diagnosis . It was recently suggested that cellular in vitro responses, determined with the lymphocyte transformation test, could discriminate between sensitized individuals with and without clinically manifest allergy .…”
Section: Patch Testingmentioning
confidence: 99%